Teori Simulacrum Jean Baudrillard pada Iklan Kecantikan “Scarlett World With Twice” dalam Komunikasi Media Massa: Analisis Semiotika Charles Sanders Pierce - Muhammad Najihul Marom; Fikri Dina Intan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The rapid development of communication and information technology has created various communication media with increasingly sophisticated tools, making humans very responsive to the information received. In the theory of simulacra by Jean Baudrillard, it is explained that the reality presented by the media is a pseudo reality, where the truth is manipulated to influence and attract people to follow it. This study aims to describe the icons, indexes, and symbols in the Scarlett Whitening advertisement on YouTube using Charles Sanders Pierce's semiotic approach. The research method used in this article is a qualitative method, with data collection techniques through in-depth observation of the advertising video. The results of this study indicate that the three aspects of trichotomy, namely icons, indexes, and symbols, in the Scarlett advertising video refer to a marketing strategy to emphasize the authenticity of the Scarlett Whitening product. This product is promoted as a product that can make days brighter like South Korean idols from the girl group Twice, while also showing that Scarlett is a trusted and effective beauty product for brightening the skin.